Quantitative prediction of magnesium absorption in dairy cows - J. T. Schonewille (2018)
The objective of the current study was to predict magnesium (Mg) absorption in dairy cows based on data from our own studies and those of other investigators. Balance data from 15 independent studies with 68 different rations and 323 dairy cows or cow-periods were used. In 12 studies, grass feeds were the main source of roughage and in about one-half of the studies, MgO-supplemented rations were used. Out of the 68 rations, 14 rations contained supplemental K in the form of bicarbonate, and in 2 rations additional K was incorporated mainly in form of KCl. The K content of the rations ranged from 6.9 to 75.6 g/kg of dry matter (DM; mean 29.4 g/kg of DM). In most studies (10/15), dry, nonpregnant cows were used. For lactating animals, milk yield ranged from 4 to 22 kg/d (mean yield, 15 kg/d). All studies provided quantitative information with respect to feed intake (DM intake, Mg, and K) and total Mg excretion in feces. The mean dietary Mg content was 4.5 g/kg of DM and ranged from 0.45 to 17.3 g/kg of DM. On average, Mg absorption (% of intake) was 26.2% and ranged from 9.9 to 73.7%. The variation in Mg absorption was at least partly explained by the variation in dietary K concentrations. Magnesium absorption (% of intake) was significantly decreased by 0.31 percentage units/g of K in the DM. To counteract the depressant effect of dietary K on Mg absorption, Mg intake must be increased by 4 g/d when the dietary K concentration increases by 10 g/kg of DM so that the amount of absorbed Mg is maintained. © American Dairy Science Association, 2008.